Pterostilbene Increases LDL Metabolism in HL-1 Cardiomyocytes by Modulating the PCSK9/HNF1α/SREBP2/LDLR Signaling Cascade, Upregulating Epigenetic hsa-miR-335 and hsa-miR-6825, and LDL Receptor Expression - Yen-Kuang Lin; Chi-Tai Yeh; Kuang-Tai Kuo; Vijesh Kumar Yadav; Iat-Hang Fong; Nicholas G. Kounis; Patrick Hu; Ming-Yow Hung (Antioxidants, 2021)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) can promote the degradation of low-density lipoprotein (LDL) receptor (LDLR), leading to hypercholesterolemia and myocardial dysfunction. The intracellular regulatory mechanism by which the natural polyphenol pterostilbene modulates the PCSK9/LDLR signaling pathway in cardiomyocytes has not been evaluated. We conducted Western blotting, flow cytometry, immunofluorescence staining, and mean fluorescence intensity analyses of pterostilbene-treated mouse HL-1 cardiomyocytes. Pterostilbene did not alter cardiomyocyte viability. Compared to the control group, treatment with both 2.5 and 5 μM pterostilbene significantly increased the LDLR protein expression accompanied by increased uptake of LDL. The expression of the mature PCSK9 was significantly suppressed at the protein and mRNA level by the treatment with both 2.5 and 5 μM pterostilbene, respectively, compared to the control. Furthermore, 2.5 and 5 μM pterostilbene treatment resulted in a significant reduction in the protein hepatic nuclear factor 1α (HNF1α)/histone deacetylase 2 (HDAC2) ratio and sterol regulatory element-binding protein-2 (SREBP2)/HDAC2 ratio. The expression of both hypoxia-inducible factor-1 α (HIF1α) and nuclear factor erythroid 2-related factor 2 (Nrf2) at the protein level was also suppressed. Pterostilbene as compared to short hairpin RNA against SREBP2 induced a higher protein expression of LDLR and lower nuclear accumulation of HNF1α and SREBP2. In addition, pterostilbene reduced PCSK9/SREBP2 interaction and mRNA expression by increasing the expression of hsa-miR-335 and hsa-miR-6825, which, in turn, increased LDLR mRNA expression. In cardiomyocytes, pterostilbene dose-dependently decreases and increases the protein and mRNA expression of PCSK9 and LDLR, respectively, by suppressing four transcription factors, HNF1α, SREBP2, HIF1α, and Nrf2, and enhancing the expression of hsa-miR-335 and hsa-miR-6825, which suppress PCSK9/SREBP2 interaction.